Customer risk and the choice between cash and bank credit lines. Issue 2 (22nd January 2022) - David, Thomas
Abstract : I use a matched buyer–supplier sample of U.S. industrial firms to investigate the impact of customer risk on suppliers' choice between cash and credit lines. I show that customer risk decreases the reliance on bank-managed liquidity insurance relative to cash. I also find evidence indicating that firms actively shy away from credit lines in response to customer risk to maximize the future availability of their liquidity reserves. Consistently, my findings suggest that high-customer-risk firms are particularly more likely to be subject to (stricter) borrowing base provisions, which tie the value of a credit line to that of some eligible collateral (notably accounts receivable). I also find that steeper credit line spreads alone cannot explain firms' response to customer risk. These results highlight how customer–supplier relationships affect the precautionary demand for liquidity, and significantly shape corporate financial decisions.